Complementary medicine research projects in Australia: 2008–2013. Issue 3 (December 2016) - Packer, Joanne; Good, Anthony; Besch, Janice; Boon, Syvilla; Bensoussan, Alan
Abstract: Objectives: Australians are among the world's highest consumers of complementary medicine. Research is vital to ensure the safe and effective use of complementary medicines and practices and their appropriate integration into mainstream healthcare. In 2014, the National Institute of Complementary Medicine (NICM) undertook a survey to determine the extent of complementary medicine academic research in Australia from 2008 to 2013. This survey builds upon aspects of previous research undertaken by NICM in 2005 and 2008. Methods: The surveys were conducted using the Survey Monkey™ program and distributed electronically by email, made available on the NICM website, provided in the NICM newsletter and sent to industry associations, who agreed to promulgate the link. The survey included 20 items assessing the size and scope of the industry in Australia in terms of the research workforce, the nature of research activities, funding mechanisms and quantum of research funds and resources and facilities available to researchers. Results: Based on survey responses reporting on the 6 year period 2008–2013, 160 respondents provided information on 295 active CM research projects employing a total quantum of $31.3 million. The greatest quantum provided for active projects came from NHMRC (36%) while universities supported the greatest number of projects (27%). 238 of the 296 projects reported on their workforce, this represented 429 academic researchers and 167 full time equivalent (FTE) research students. $29.5M in new funding was awarded to new projects over this period. Conclusions: Whilst the total reported quantum of research funding for expenditure on CM projects in the period January 2008–December 2013 was $31.3M, the annual funding of new CM research projects decreased considerably in the latter part of the survey period. Australia has a well-developed CM research sector; however it is insufficiently supported given the size of the Australian industry and the level of consumer use.